Beyond Colonial Legacies: (Re)Conceptualising Rural Development Through the RDGI in South Africa - Kgomotso Jackson Phillip Sebola-Samanyanga (Land)
Despite constitutional recognition, significant barriers remain to the integration of traditional authorities into formal planning and development decision-making processes in South Africa. Observing resistance from traditional authorities towards what they deem as exclusive and restrictive planning instruments, this study interrogates the intricate power dynamics between traditional leadership structures and imposed local government entities in rural development, planning, and governance processes to propose a cooperative governance framework within the South African context. The proposed framework is termed the “Rural Development and Governance Initiative” (RDGI), which aims to bridge the divide between traditional and local authorities. This study applied qualitative methods to investigate the relations between authorities in Limpopo province, South Africa. The findings reveal ongoing disputes between traditional and local authorities regarding decision-making powers, legitimacy in development and planning, and the capacity limitations and constraints faced by traditional authorities. The implications of this work extend to the (re)conceptualisation of policies and future research directions in rural governance, land development, and planning in South Africa, advocating for a shift from foreign models to those that reflect African realities and aspirations.